2018
DOI: 10.1111/iju.13563
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen screening impacts on biochemical recurrence in patients with clinically localized prostate cancer

Abstract: Detection by screening results in favorable outcomes after surgery. Prostate-specific antigen screening might contribute to reducing biochemical recurrence in patients with localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…A previous hospital‐based cohort study reported that 73.5% of patients aged 55–69 years were identified by PSA testing, and these patients had a better prognosis than those diagnosed with local and/or systemic symptoms, and a similar result was obtained from another Japanese population screening cohort study, in which the prognosis of prostate cancer patients detected by population screening was shown to be more favorable than that for those diagnosed outside of population screening . These findings reflected earlier detection of prostate cancer using PSA testing in all stages of prostate cancer; however, the present study showed that pathological features of cancer and biochemical recurrence‐free survival were more favorable in patients identified through PSA screening than patients who underwent PSA testing at a urology clinic for clinically localized prostate cancer . As described, higher age, PSA levels and prostate volume possibly lead to poorer clinical outcomes.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…A previous hospital‐based cohort study reported that 73.5% of patients aged 55–69 years were identified by PSA testing, and these patients had a better prognosis than those diagnosed with local and/or systemic symptoms, and a similar result was obtained from another Japanese population screening cohort study, in which the prognosis of prostate cancer patients detected by population screening was shown to be more favorable than that for those diagnosed outside of population screening . These findings reflected earlier detection of prostate cancer using PSA testing in all stages of prostate cancer; however, the present study showed that pathological features of cancer and biochemical recurrence‐free survival were more favorable in patients identified through PSA screening than patients who underwent PSA testing at a urology clinic for clinically localized prostate cancer . As described, higher age, PSA levels and prostate volume possibly lead to poorer clinical outcomes.…”
supporting
confidence: 82%
“…In this issue of the International Journal of Urology , Hashimoto et al . examined the impact of prostate‐specific antigen (PSA) screening in patients with clinically localized prostate cancer undergoing robot‐assisted radical prostatectomy . They hypothesized that the lower rate of PSA screening in Japan led to poorer prognosis after radical prostatectomy in previous Japanese cohorts, and showed that patients diagnosed based on a PSA screening test tended to have cancers in an early phase …”
mentioning
confidence: 99%
“…1 Radical prostatectomy is considered as the first-line treatment option for PCa patients, but recurrence (biochemical, BCR; or clinical) frequently occurs in 10-40% of patients after curative surgery, [2][3][4] which leads to the cumulative 5-year recurrence-free survival (RFS) rate of only about 65%. 3,5 Clinically, prostate-specific antigen (PSA) level, 6 Gleason score, 7 and tumor, node, metastasis (TNM) staging 8 are widely used to predict tumor recurrence. Nevertheless, their prediction accuracy remains unsatisfactory (<70%).…”
Section: Introductionmentioning
confidence: 99%